FAMILIES RESILIENCE WITH RECOVERY ADDICT IN SUMEDANG UTARA DISTRICT SUMEDANG REGENCY INDONESIA - Atirista Nainggolan (Indonesian Journal of Social Work, 2022)
This research is motivated by substance abuse in Indonesia worrying increasingly year by year. Substance abuse is a threat to Indonesia, especially at a productive age, and affects family resilience. The family resilience of recovery addict is the family in facing all living conditions to achieve an independent life and improve family welfare. Research on " Families Resilence with recovery addict in Sumedang Utara Sub-district, Sumedang Regency" is a case study that aims to determine how the resilience of families who have family members of drug abuse is seen from the aspects of physical endurance, social resilience, and psychological resilience. The method used in this research is descriptive method with a qualitative approach based on the interpretation of primary data and secondary data. The informants in this research consisted of 4 families who have family members of drug abuse victims. The data collection techniques used consisted of: (1) in-depth interviews, (2) observation, (3) documentation study. The results showed that the four informants gave varied answers. Judging from the aspect of physical resilience, there is 1(one) family that does not fulfill its basic needs, including clothing, food, shelter, education, and health. Other informants, namely 3(three) families can fulfill basic needs well. From the aspect of social resilience, the informants indicated that 3 families could not spend time maximally with other family members and 1(one) other family could spare time. Meanwhile, from the psychological aspect, 3 (three) families were unable to control anger and disappointment and 1(one) family was able to control emotions towards family members of substance abuse.